Phytochemical Analysis and Antimicrobial Activity of Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. Fruit Extracts Against Gastrointestinal Pathogens: Enhancing Antibiotic Efficacy - Gagan Tiwana; Ian Edwin Cock; Matthew James Cheesman (Microorganisms)
Terminalia bellirica (Gaertn) Roxb. and Terminalia chebula Retz. are significant botanicals in ancient Ayurvedic medicine. They are renowned for their therapeutic properties, notably in addressing gastrointestinal (GI) diseases. These plants have undergone thorough examination related to their antibacterial, anti-inflammatory, and antioxidant properties, which make them highly efficient natural treatments for controlling gastrointestinal infections. The current research demonstrated the antibacterial efficacy of fruit extracts of Terminalia bellirica and Terminalia chebula against Bacillus cereus, Shigella sonnei, Shigella flexneri, and Salmonella typhimurium. We performed disc diffusion and liquid microdilution experiments to evaluate the antibacterial efficacy. All extracts of Terminalia bellirica and Terminalia chebula showed good antibacterial effects against B. cereus and S. flexneri. The minimum inhibitory concentration (MIC) values ranged from 94 µg/mL to 556 µg/mL. The methanolic extracts from both plants also showed noteworthy antibacterial activity against S. sonnei and S. typhimurium, with MIC values of 755 µg/mL for both. Fractional inhibitory concentration studies revealed additive interactions between some conventional antibiotics and the plant extracts when used concurrently. Liquid chromatography–mass spectrometry (LC-MS) analyses revealed that the T. bellirica and T. chebula extracts contained various tannins including methyl gallate, propyl gallate, gallic acid, and ellagic acid. Lethality assays conducted using Artemia franciscana Kellogg nauplii indicated that all the plant extracts are non-toxic. The antibacterial properties and absence of toxicity in T. bellirica and T. chebula fruit extracts indicate their potential for antibiotic development, warranting additional mechanistic and phytochemical studies.